THE IMPACT OF DISTRIBUTION OF PUBLIC BUSINESS CREDIT (KUR) FOR MICRO, SMALL AND MEDIUM ENTERPRISES (UMKM) CUSTOMERS OF PT. BANK MANDIRI SUPPORT BRANCH OFFICE (KCP) MANDIRI PARTNER BUSINESS (MMU) PASAR SINAKMA JAYAWIJAYA DISTRICT - Ali, Muhammad; Haryati, Tati; *, Aprilia (The International Journal of Accounting and Business Society, 2021)
AbstractThe purpose of KUR is to increase access to finance for Small and Medium Enterprises (UKM) to financial institutions with a guarantee scheme through the People's Business Credit (KUR). The KUR guarantee is provided in order to increase UMKM access to sources of financing in order to encourage national economic growth. Bank Mandiri is one of the State-Owned Enterprises (BUMN) that was established to assist UMKM players in realizing their business and maintaining business continuity. The results showed that with the existence of a program from the government through the distribution of People's Business Credit which was channeled through PT. Bank Mandiri KCP MMU Wamena Pasar Sinakma for the welfare of Micro, Small, and Medium Enterprises (UMKMÂ Keywords: People's Business Credit, UMKM